2022
DOI: 10.1177/15353702221089910
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical studies of bintrafusp alfa, a novel bifunctional anti-PD-L1/TGFβRII agent: Current status

Abstract: Bintrafusp alfa (anti-PD-L1/TGFβRII) is a first-in-class bifunctional agent designed to act both as a checkpoint inhibitor and as a “trap” for TGFβ in the tumor microenvironment (TME). This article is designed to review the preclinical studies interrogating the mode of action of bintrafusp alfa and to present a comprehensive overview of recent bintrafusp alfa clinical studies. Preclinical studies have demonstrated that bintrafusp alfa immune-mediating and antitumor activity can be enhanced by combining it with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Treatment-related adverse events were observed in 4 out of 19 patients and the maximum tolerated dose (MTD) was not determined. Previous clinical trial findings using bintrafusp alfa have been well-described in other publications (75,76).…”
Section: Landscape Of Immune Checkpoint Blockade Beyond Targeting Ctl...mentioning
confidence: 59%
See 1 more Smart Citation
“…Treatment-related adverse events were observed in 4 out of 19 patients and the maximum tolerated dose (MTD) was not determined. Previous clinical trial findings using bintrafusp alfa have been well-described in other publications (75,76).…”
Section: Landscape Of Immune Checkpoint Blockade Beyond Targeting Ctl...mentioning
confidence: 59%
“…Bintrafusp alfa, previously known as M7824, is a first-in-class bifunctional fusion protein that consists of an anti-PD-L1 antibody covalently linked to the extracellular domain of two TGF-βRII molecules that is designed to block the PD-1/PD-L1 axis while also sequestering TGF-β molecules ( 75 , 76 ). Several preclinical studies have confirmed the antitumor efficacy of bintrafusp alfa and its ability to increase the immune response in triple negative breast, bladder, and HPV + cervical cancer models ( 77 , 78 ).…”
Section: Non-specific Targeting Of the Tmementioning
confidence: 99%
“…Preclinical studies conducted on murine models have demonstrated the robust inhibitory effect of bintrafusp alfa on tumor growth and metastasis compared to that of TGF-β and PD-L1 inhibitors [ 189 ]. Preliminary clinical research has further indicated that bintrafusp alfa can improve the outcomes in patients with HPV + malignancies, including those exhibiting ICI resistance [ 190 ]. A phase I/II trial of bintrafusp alfa treatment was conducted in patients having HPV + solid tumors, including cervical cancer, anal cancer, and P16 + head and neck squamous cell carcinoma.…”
Section: Digestive System Tumorsmentioning
confidence: 99%
“…Bintrafusp alfa combines the extracellular domain of the human transforming growth factor‐β receptor II with an IgG1 antibody that blocks programmed cell death ligand 1 (anti‐PD‐L1) 20 . Studies have demonstrated that bintrafusp alfa enhances therapeutic efficacy and survival rates compared to the administration of the anti‐PD‐L1 antibody alone 21 . Similarly, latikafusp is an antibody targeting programmed cell death protein 1 fused with a mutated interleukin 21 (IL‐21) cytokine 22 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Studies have demonstrated that bintrafusp alfa enhances therapeutic efficacy and survival rates compared to the administration of the anti-PD-L1 antibody alone. 21 Similarly, latikafusp is an antibody targeting programmed cell death protein 1 fused with a mutated interleukin 21 (IL-21) cytokine. 22 Furthermore, latikafusp has also shown promising results, suggesting that antibodies fused with IL-21 cytokine can improve efficacy and reduce cytokine off-target effects.…”
mentioning
confidence: 99%